Initial conservative management strategy of HeartWare left ventricular assist device thrombosis with intravenous heparin or bivalirudin. Issue 7 (July 2020) - Bouzas-Cruz, Noelia; Gonzalez-Fernandez, Oscar; Ferrera-Durán, Carlos; Woods, Andrew; Robinson-Smith, Nicola; Tovey, Sian; Jungschleger, Jérôme; Booth, Karen; Shah, Asif; Parry, Gareth; MacGowan, Guy A; Schueler, Stephan
Introduction and objectives: Pump thrombosis is a serious left ventricular assist device complication, though there are no guidelines regarding its treatment. The main aim of this study was to describe a strategy of intravenous anticoagulation as the initial treatment in these patients and then to compare intravenous heparin with bivalirudin. Methods: All consecutive patients who received a HeartWare left ventricular assist device from July 2009 to March 2019 were retrospectively analysed. Patients developing a pump thrombosis were selected, and treatment, outcomes and complications were recorded. Results: During this period of time (116 months), 220 patients underwent HeartWare left ventricular assist device implantation and 57 developed pump thrombosis, with an incidence rate of first pump thrombosis of 0.17 events per patient-year of support (incidence rate of all episodes of pump thrombosis: 0.30 events per patient-year of support). All the patients were initially treated medically, predominantly with either intravenous heparin (n = 26) or bivalirudin (n = 16). Patients treated with bivalirudin during the first pump thrombosis episode had less subsequent re-thrombosis episodes (18.7% vs 57.7%, p < 0.05). In addition, percentage time in therapeutic range was greater for bivalirudin compared with heparin (68.5% ± 16.9% vs 37.4% ± 31.0%, p < 0.01). During the first pump thrombosis episode, 26.3% of the patients needed surgery (left ventricular assist device exchange (n = 8), transplant (n = 6) or decommissioning (n = 1)). The overall survival at 1 year was 61.4%, and there was no significant difference in survival. Conclusion: Left ventricular assist device thrombosis is a serious life-threatening complication; hence, we propose an initial conservative management of pump thrombosis with enhanced intravenous anticoagulation with either intravenous heparin or bivalirudin, with surgery reserved for refractory cases.